MENINGKATKAN KEMAMPUAN MENYELESAIKANSOAL DENGAN METODE PROBLEM SOLVING DALAM PEMBELAJARAN MATEMATIKA PADA SISWA KELAS 1 SD NEGERI PUJOKUSUMAN 1 SEMESTER GENAP TAHUN AJARAN 2013-2014 - Dewi Andriyani (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
This research aims to improve the learning results operation count through the Method of Problem Solving.Subject research is teacher and students off class 1 Pujokusuman elementary school, Keparakan, Mergangsan Yogyakarta.Research instruments validated the approval from expert judgment. Data research collected by a test and a observation. Data analysis should be conducted in every cycles. Quantitative data analyzed using analysis descriptive quantitative. Qualitative analyzed data on using analysis descriptive qualitative with a step reduction data, exposure, and resume. This result of the study provide a there is an increase study results operation count, through a method of the problem Solving. This increase seen in the Minimal Achievement Criteriaat least which was originally at the cycle of 46, 25 % to 86, 43 in the cycle to two.